Identifying opportunities to improve quality of cooked sausages by optimizing their recipes - Orymbetova, Gulbagi; Kassymova, Makhabat; Orymbetov, Emit; Abish, Zhansaya (Eastern-European Journal of Enterprise Technologies, 2025)
The object of the study is recipe for sausage products with addition of pea flour. The problem being solved is to create meat products with an optimal composition and quality with improved organoleptic nutritional characteristics while maintaining safety and technological effectiveness of product. During study, a mathematical model for optimizing recipe was constructed using the linear programming method, and qualimetric assessment of the quality of final product was carried out. The optimal composition of sausage products consists of the following: beef – 820 g/kg; lamb fat – 80 g/kg; pea flour–53.35 g/kg; table salt – 1.5 g/kg; sodium nitrite – 0.002 g/kg; ground black pepper–0.1 g/kg; starch – 45 g/kg; sugar – 0.15 g/kg. The results of the study showed that complex quality indicator is 0.88. It corresponds to the best indicator of quality of finished products. The values of group quality indicators of cooked sausages are as follows: organoleptic indicators – 0.14; physicochemical indicators – 0.14, safety indicators – 0.36, nutritional value – 0.15, energy value – 0.09. By using these approaches to selecting ingredients and their quantitative ratios, it was possible to achieve balance in amino acid and fat composition, reduce cost price and improve organoleptic characteristics of the product. These results are explained by use of a set of methods of mathematical modeling and organoleptic correction of the recipe based on tasting assessment. Using pea flour reduces raw material costs, it would be appropriate to use it as an alternative to meat. The data obtained can be used in practice in development of functional meat products, especially in context of the need to increase nutritional value, safety and competitiveness of products